السياسة العقابية الجديدة لتدعيم السلامة المرورية وأمنها - بن خليفة ., إلهام (University of Eloued جامعة الوادي, 2021)
ملخص: يتبين من الترسانة القانونية التي وضعت في الجزائر لتدعيم السلامة المرورية وأمنها عبر الطرقات نية المشرع في التصدي لظاهرة حوادث المرور المرعبة، وذلك بمحاولة إيجاد حلول لها وبلوغ التطور الذي وصلت إليه الدول المتقدمة، حيث لم يكتف بتشديد العقاب على المخالفين لقانون تنظيم حركة المرور عبر الطرق وسلامتها وأمنها فحسب، بل راح لأبعد من ذلك وانتهج السياسة الوقائية باستحداثه لنظام الرخصة بالنقاط، وتطرح هذه الورقة البحثية اشكالية مدى فعالية الجزاءات الجنائية الحديثة في محاولة الحد من حوادث المرور، وللإجابة على هذه الإشكالية تضمنت الدراسة قراءة قانونية في نظام الرخصة بالنقاط وكذا عقوبات الجنح والغرامات الجزافية للمخالفات. Abstract The established legal arsenal in Algeria in strengthening traffic safety and security across roads indicates the intention of the legislator to address the horrific phenomenon of traffic accidents, by trying to find solutions to them and achieve the development the same as developed countries. The legislator was not satisfied with tightening the punishment for violators of the law on road traffic regulation and safety not only its security but also went beyond that and he pursued the preventive policy by introducing the license by point system. This research paper raises the problem of the effectiveness of modern criminal penalties in trying to reduce traffic accidents, and to answer this problem, the study included a legal reading in the license system by points, as well as misdemeanor penalties and fixed fines for irregularities.
The punitive policy for strengthening traffic safety and security
مقال
Keywords: حوادث المرور؛ نظام الرخصة بالنقاط؛ جنح ومخالفات؛ عقوبات مشددة؛ غرامات جزافية.; Traffic Accidents; Point license system; Misdemeanors and infractions; Heavy penalties; fixed fines.